Caracterização anátomo-patológica do músculo pectoralis major de frangos de corte acometidos com White Striping e Wooden Breast - Teixeira, Sabrina Tolotti Fraga (2015)
The Brazil since 2004 has an important role in poultry international, so the search for production technologies and increasingly efficient sanitary conditions are key to staying on top of the list of export of chicken meat. This work aims to carry out an analysis of the incidence of convictions from Federal Inspection lines, and the anatomical and histopathological characterization of the Pectoralis major muscle affected by injuries of White Striping and Wooden Breast, both degenerative myopathy of unknown etiology, and with a strong relation to fast growth rates in chickens still associated with the high weight of the birds. Collecting data and samples were performed at three different companies, with chickens of the Cobb with minimum weight 1100 g and a maximum of 4376g, both for marketing of cuts as whole carcasses. Birds with mixed lots (males and females) and just lots of males or females, with age at least 34 days and a maximum of 45 days. The incidence of lesions of White striping was 0.18% and Wooden breast was 0.54% difference in results between companies which suggest that nutritional factors or management may be influencing the occurrence of these myopathies. Macroscopically both carcasses lesions are characterized by hypertrophy and muscle rigidity Pectoralis major and gastrocnemius. Cutting of the skin it was possible to identify the lesion of White striping primarily by the presence of whitish streaks in the direction of the muscle fibers, while the Wooden breast lesion beyond the presence of the white striping was possible to realize a bulging primarily in the flowrate of the steak, but a pale yellowish appearance of the muscles. The optical microscopy, both showed similarities as regards myopathies histological abnormalities, characterized by a miodegeneração process. It was observed that in fillets with Wooden breast, connective tissue of the mole was more aggressive when compared with White striping where interstitial infiltrate of adipose tissue was more evident